2020
DOI: 10.1007/s11252-020-00956-w
|View full text |Cite
|
Sign up to set email alerts
|

Bee community response to local and landscape factors along an urban-rural gradient

Abstract: Over a third of the world's crops require insect pollination, and reliance on pollination services for food continues to rise as human populations increase. Furthermore, as interest in urban agriculture has grown, so has a need for studies of urban pollinator ecology and pollination. Analyzing pollinator assemblages along a rural-urban gradient provides powerful mechanistic insight into how urbanization impacts pollinators. Yet, studies examining pollinators along urban-rural gradients are limited and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 83 publications
3
12
0
Order By: Relevance
“…Like the majority of bees found in cities (MacIvor et al, 2014;Matteson et al, 2008), B. impatiens is a diet generalist that is known to forage on a large number of plant species (Colla & Dumesh, 2010;Gervais et al, 2020;Vaudo et al, 2014), including many that attract other native pollinators. For for other bumblebee species (Jha & Kremen, 2013a,b) and native bee communities (Bennett & Lovell, 2019;Birdshire et al, 2020;Egerer et al, 2020;Fortel et al, 2014;Geslin et al, 2016). Similarly, functional green space in Toronto was associated with shorter foraging distances in our RDA analysis, which is consistent with previous research on the importance of forage for many other native bumblebees (Carvell et al, 2011(Carvell et al, , 2012(Carvell et al, , 2017Goulson et al, 2010;Redhead et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Like the majority of bees found in cities (MacIvor et al, 2014;Matteson et al, 2008), B. impatiens is a diet generalist that is known to forage on a large number of plant species (Colla & Dumesh, 2010;Gervais et al, 2020;Vaudo et al, 2014), including many that attract other native pollinators. For for other bumblebee species (Jha & Kremen, 2013a,b) and native bee communities (Bennett & Lovell, 2019;Birdshire et al, 2020;Egerer et al, 2020;Fortel et al, 2014;Geslin et al, 2016). Similarly, functional green space in Toronto was associated with shorter foraging distances in our RDA analysis, which is consistent with previous research on the importance of forage for many other native bumblebees (Carvell et al, 2011(Carvell et al, , 2012(Carvell et al, , 2017Goulson et al, 2010;Redhead et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Impervious structures (e.g., roads, buildings, and other paved surfaces) had a clear negative impact on both B . impatiens ’ colony density and foraging distance in our analysis; similar detrimental effects of impervious surfaces have been documented for other bumblebee species (Jha & Kremen, 2013a , 2013b , 2013a , 2013b ) and native bee communities (Bennett & Lovell, 2019 ; Birdshire et al, 2020 ; Egerer et al, 2020 ; Fortel et al, 2014 ; Geslin et al, 2016 ). Similarly, functional green space in Toronto was associated with shorter foraging distances in our RDA analysis, which is consistent with previous research on the importance of forage for many other native bumblebees (Carvell et al, 2011 , 2012 , 2017 ; Goulson et al, 2010 ; Redhead et al, 2016 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Some studies found that urban areas could be hotspots for bees (Baldock et al, 2015; Theodorou et al, 2020), but others found that they contributed to their decline (Bates et al, 2011; Geslin, Le Féon, et al, 2016; Pereira et al, 2021). Within urban areas, bee communities are affected by different biotic and abiotic drivers, such as urban warming and pollution (Hamblin et al, 2018) and other environmental factors ranging from local to landscape scales (Birdshire et al, 2020). Within their local habitats, flower cover and floral richness enhance their diversity (Bates et al, 2011; Hülsmann et al, 2015; Theodorou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These aspects of urban landscapes can allow cities to harbour diverse pollinator communities (Baldock et al 2015;Fortel et al 2014;Geslin et al 2015). Despite a growing interest in urban pollinator diversity (Banaszak-Cibicka et al 2018;Birdshire et al 2020) and pollination services (Harrison and Winfree 2015;Wenzel et al 2020), very few studies assess whether these unique urban pollinator communities can provide su cient pollination services to support urban crop production.…”
Section: Introductionmentioning
confidence: 99%